Vida religiosa consagrada e velhice : cognição, funcionalidade e necessidade de cuidado - Mozer, Neuza Maria Sangiorgio (2013)
The longevity is achieved by an increasing number of people defying family and society to care of your life. This study focused on the aging scenario of consecrated religious life (VRC) female on the need for long-term care (CLD). The general objective was to analyze factors associated with health conditions in older women in need of long-term care, members of religious congregations. The study is cross-sectional population-based sample consisting of fifty elderly religious. Inclusion criteria were having established sixty years or more and be residing in the homes of recognized institutions for CLD independent caregiver or be in need of care, besides presenting a position to respond to the proposed instruments. Data collect took place from October 2011 to January 2012 by the researcher using a structured questionnaire, in which the interview was recorded, which is divided into six sections: personal information, health conditions, medications, cognitive valuation, dietary habits and occupation of free time. Part of the results was compiled in two scientific productions, both attached to this text. The first entitled Cognitive performance and symptoms of depression among elderly religious women aimed to investigate cognitive performance and factors associated with depression in this group of women, using the Mini Mental State Examination (MMSE) and the Geriatric Depression Scale (GDS-15). Outcome data were analyzed using the Mann-Whitney and chi-square test, for a significance level of p ≤ 0.05 and confidence interval (CI) of 95%, resulting in significant MMSE score for the variables range age, time of religious life, years of study and need for care. The GDS-15 showed 87.8% of individuals scoring positive for depression. The scientific II titled Care needs and functionality among elderly religious women aimed to evaluate the need for careful self-reported and functionality of these elderly through the Katz Index, verifying the independence to perform their activities of daily living (ADLs). Data were assessed by the Mann-Whitney and chi-square for a significance level of p ≤ 0.05 and confidence interval (CI) of 95%, with statistical significant results for the variables bathing, dress up and go to the bathroom. It appears that although the high average education is important index of cognitive decline and depression in the population studied and identified some factors associated with these prevalences such as high care needs and age. Another evidence is that even referring to the need for care, the elderly nuns allow themselves to maximum self-care. The research took place without difficulty, however, presents limitations because it is a specific context that cannot be generalized. The results indicate the need for further studies in this scenario in view of aging as a progressive process within their religious congregations.